Music symbol recognition - Ooi, Joyce Boon Ee; Tan, Alan W. C. (2011)
This paper focuses on optical music recognition (OMR) system that recognizes the musical symbols on a digitized music sheet and converts them into symbolic music representation. Two main stages are distinguished ? pre-processing and symbol analysis. In the pre-processing stage, staves are detected and removed; while in the symbol analysis stage, each musical symbol is recognized and analyzed. The musical semantics are then determined and converted into symbolic music representation stored in text form.